Chemical Vapor Deposition of Monolayer Rhenium Disulfide (ReS2). (3rd July 2015) - Keyshar, Kunttal; Gong, Yongji; Ye, Gonglan; Brunetto, Gustavo; Zhou, Wu; Cole, Daniel P.; Hackenberg, Ken; He, Yongmin; Machado, Leonardo; Kabbani, Mohamad; Hart, Amelia H. C.; Li, Bo; et al.
<x xml:space="preserve">Abstract</x> The direct synthesis of monolayer and multilayer ReS2 by chemical vapor deposition at a low temperature of 450 °C is reported. Detailed characterization of this material is performed using various spectroscopy and microscopy methods. Furthermore initial field‐effect transistor characteristics are evaluated, which highlight the potential in being used as an n‐type semiconductor.